الكفاءة البدنية ومستوى الأداء المهارى الهجومي وعلاقتهما بمفهوم الذات البدنية لدى لاعبي كرة القدم - حسين، حسن جاسم; عليوي، ياسر محسن; الزبيدي، وسام قيس خزعل نجم (جامعة بابل - كلية التربية الرياضية, 2020)
يعد الجانب النفسي أحد المتطلبات الأساسية في لعبة كرة القدم الذي يعمل على إخراج اللاعب بشكل أفضل من ناحية الأداء البدني والمهاري والخططي وتتميز لعبة كرة القدم بتعدد مهاراتها وتسلسلها فضلا عن ترابطها الذي يجعل اعتماد كل مهارة على التي تليها وبهذا سيزيد من فاعلية العامل النفسي، وللأداء الحركي الدقيق بالغ الأهمية في لعبة كرة القدم حيث أن مواقف اللعب تتغير من الهجوم إلى الدفاع مما ستلزم توظيفها بشكل أمثل لمتطلبات اللعب للسيطرة على مجريات اللعب، كما أن مفهوم الذات البدنية تعني تقدير اللاعب للصفات البدنية التي يمتلكها حيث أن الرياضي يجب أن يدرك ما يتمتع به من صفات بدنية ومهارية وأن تكون لديه الثقة العالية بالقدرات التي يمتلكها لتساعده على مواجهة المواقف المختلفة وخاصة في المنافسات الرياضية، وتكمن أهمية البحث في محاولة دراسة الجانب البدني الواقعي للرياضي ومدى علاقته بالذات البدنية في الجانب الرياضي، ومكانية توظيف معرفة اللاعب بقدراته البدنية ولصالح الأداء المهاري ومواجهة المواقف المختلفة في المنافسات الرياضية، أما مشكلة البحث لقد لاحظ الباحثون من خلال اطلاعهم على أدبيات فسلجة التدريب الرياضي أن هناك ندرة في الدراسات التقويمية التي تتناول علاقة الارتباط بين الكفاءة البدنية والمهارات الهجومية ومستوى مفهوم الذات حيث تكمن مشكلة البحث في عدم معرفة اللاعبين بمستوى قدراتهم في الجانب البدني والمهاري والنفسي ومدى العلاقة بينهما فخلال إجراء اختبار الكفاءة البدنية والأداء المهاري للاعب ودراسة علاقة ذلك بما يدركه اللاعب من امتلاكه الصفات البدنية ومدى فهمه الدقيق لهذه الصفات التي تؤهله من اجتياز العقبات التي تواجهه خلال المنافسات الرياضية بثقة، أما أهم الأهداف التعرف على مستوى الكفاءة البدنية والأداء المهاري وعلاقتهما بتقدير مفهوم الذات البدنية لدى لاعبي كرة القدم، أما فرض البحث يوجد ارتباط إيجابي بين مستوى الكفاءة البدنية والأداء المهاري بتقدير مفهوم الذات البدنية لدى لاعبي كرة القدم أما عينة البحث أجري البحث على عينة اختيرت بالطريقة العمدية تكونت من (11) لاعبا من لاعبي نادي السكر الرياضي حيث كان مجتمع البحث (20) لاعبا، أما أهم الاستنتاجات وجود علاقة ارتباط ذات دلالة معنوية بين مفهوم الذات البدنية ومستوى الكفاءة البدنية وهذا يفسر أن عينة البحث يدركون ما يمتلكونه من قدرات بدنية وتطبيق ذلك في الواقع، أما أهم التوصيات إمكانية استخدام المقياس المطبق في البحث الحالي من قبل المدربين لقياس تقدير الذات البدنية. The psychological aspect is one of the basic requirements in the game of football, which works to bring out the player better in terms of physical, skill and planning performance. The game of football is characterized by the multiplicity of its skills and sequences as well as its interconnectedness that makes each skill dependent on the next, and this will increase the effectiveness of the psychological factor, and for accurate motor performance is extremely important in the game of football as the positions of the game change from attack to defense, which will need to be optimized for the requirements of play to control the course of the game. The concept of the physical self means the player's appreciation of the physical qualities he possesses, as the athlete must realize what he enjoys from Physical and skillful qualities and to have high confidence in the abilities he possesses to help him face different situations, especially in sports competitions. The research significance lies in trying to study the realistic physical side of the athlete and the extent of his relationship with the physical self in the sports side, and the possibility of employing the player's knowledge of his physical abilities and for the benefit of skillful performance and facing situations. As for the research problem , researchers have noticed, through their review of the literature, of the Riyadh training series That there is a dearth of evaluation studies that deal with the relationship between physical competence, offensive skills and the level of self-concept, where the problem of research lies in the lack of knowledge of the players with the level of their abilities in the physical, skill and psychological aspect and the extent of the relationship between them during the examination of the physical aptitude and the skill performance of the player and studying the relationship of that with what he perceives the player's possession of physical qualities and the extent of his accurate understanding of these qualities that qualify him to pass the obstacles that he faces during sports competitions with confidence. The researcher aimed to identify the level of physical competence and skillful performance and their relationship to the appreciation of the concept of physical self among football players. As for the research hypothesis is that there is a positive correlation between the level of Physical competence and skill performance in assessing the concept of physical self among football players. As for the research sample, the research was conducted on its own sample. It was deliberately chosen. It consisted of (11) players from the Sugar Sports Club where the research community was (20) players. As for the most important conclusions, there is a significant correlation relationship between the concept of the physical self and the level of physical competence, and this explains that the research sample is aware of the physical abilities they possess. In fact, the most important recommendations are the possibility of using the scale applied in the current research by trainers to measure physical self-esteem.
Keywords: الأداء المهاري -- الخطط الهجومية -- اللياقة البدنية -- لاعبو كرة القدم